Mursyid-Salik sebagai Pendidik Akhlak : Tinjauan Epistemologi Pendidikan Islam - Kurnianingsih, Nia; Mega, Hadistia; Rahmi Puspitaningsih, Hafifah (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
Amidst the challenges of moral degradation in the digital era, Islamic education requires a holistic approach that goes beyond cognitive transfer to encompass spiritual dimensions. This study aims to analyze the role of the mursyid-salik as a moral educator through the lens of Islamic educational epistemology, particularly the integration of three approaches: bayani (textual), irfani (spiritual), and burhani (rational). A qualitative research method with a library research approach was employed to analyze classical Sufi texts (such as Ihya Ulumuddin and Al-Hikam) and contemporary literature. The findings reveal that the mursyid-salik synergistically combines these three epistemologies, with bayani serving as the normative foundation, irfani facilitating inner transformation through dhikr and spiritual retreats, and burhani fostering rational awareness. The moral development model comprises three stages: takhalli (self-purification), tahalli (embellishment with virtues), and tajalli (manifestation of divine values). These findings affirm that the mursyid-salik's approach offers a comprehensive solution to contemporary moral crises by integrating role modeling, spiritual experiences, and critical reasoning. The study concludes by recommending the integration of this model into modern Islamic education curricula, while acknowledging challenges such as public misconceptions and the digitalization of spiritual guidance.